2018
DOI: 10.1136/gutjnl-2017-314600
|View full text |Cite
|
Sign up to set email alerts
|

Gastritis staging in the endoscopic follow-up for the secondary prevention of gastric cancer: a 5-year prospective study of 1755 patients

Abstract: This prospective study confirms that OLGA staging reliably predicts the risk for development of gastric epithelial neoplasia. Although no neoplastic lesions arose in naïve patients, the eradication in subjects with advanced stages (III-IV) did not abolish the risk for neoplastic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
104
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 47 publications
5
104
0
13
Order By: Relevance
“…Operative link on gastritis assessment (OLGA) staging estimates the risk for GC in progressive stages (0‐IV). In a prospective study performed on a cohort of 1755 consecutive dyspeptic patients with a median follow‐up of 55 months, Rugge et al confirmed that OLGA gastritis staging is reliable in predicting the risk for gastric epithelial neoplasia development. After initial endoscopy with mapped gastric biopsies, OLGA staging, and assessment of H. pylori infection, patients with stages II III and IV underwent a second endoscopy with restaging, whereas those with stages 0 and I were followed clinically.…”
Section: Gastric Cancer: Prevention Strategies/screening For Preneoplmentioning
confidence: 97%
“…Operative link on gastritis assessment (OLGA) staging estimates the risk for GC in progressive stages (0‐IV). In a prospective study performed on a cohort of 1755 consecutive dyspeptic patients with a median follow‐up of 55 months, Rugge et al confirmed that OLGA gastritis staging is reliable in predicting the risk for gastric epithelial neoplasia development. After initial endoscopy with mapped gastric biopsies, OLGA staging, and assessment of H. pylori infection, patients with stages II III and IV underwent a second endoscopy with restaging, whereas those with stages 0 and I were followed clinically.…”
Section: Gastric Cancer: Prevention Strategies/screening For Preneoplmentioning
confidence: 97%
“…7,8 Several studies show a diminished risk of GC with low OLGA stages (0, I, II) and high risk of GC with high OLGA stages (III, IV). [9][10][11][12] Recently, the operative link on gastric intestinal metaplasia assessment (OLGIM) staging system, which replaces the atrophy score with IM score, was proposed and is associated with a high inter-observer agreement. 13 However, OLGA or OLGIM systems require biopsy and they need to be validated whether these invasive systems are effective enough to estimate the risk of GC not only for the intestinal type but also for the diffuse type.…”
mentioning
confidence: 99%
“…Furthermore, 53% of stage II cases did not change, 19% progressed to stage III, and only 28% returned to stage 0 or I. 32 These recent reports show that even in patients with gastritis in treatment-responsive stages, the recovery time is long, and there are certainly cases that still progress to gastric cancer even after H pylori eradication.…”
Section: Logical Lead Time From the Eradication Of H Pylori To A Rementioning
confidence: 91%